Genomic variability in Zika virus in GBS cases in Colombia. - Nelson Rivera-Franco; Diana López-Alvarez; Andrés Castillo; Erica Aristizabal; Daniela Puiu; Steven L Salzberg; Carlos A Pardo; Beatriz Parra; NEAS (PLoS ONE)
Major clusters of Guillain-Barré Syndrome (GBS) emerged during the Zika virus (ZIKV) outbreaks in the South Pacific and the Americas from 2014 to 2016. The factors contributing to GBS susceptibility in ZIKV infection remain unclear, although considerations of viral variation, patient susceptibility, environmental influences, and other potential factors have been hypothesized. Studying the role of viral genetic factors has been challenging due to the low viral load and rapid viral clearance from the blood after the onset of Zika symptoms. The prolonged excretion of ZIKV in urine by the time of GBS onset, when the virus is no longer present in the blood, provides an opportunity to unravel whether specific ZIKV mutations are related to the development of GBS in certain individuals. This study aimed to investigate the association between specific ZIKV genotypes and the development of GBS, taking advantage of a unique collection of ZIKV-positive urine samples obtained from GBS cases and controls during the 2016 ZIKV outbreak in Colombia. Utilizing Oxford-Nanopore technology, we conducted complete genome sequencing of ZIKV in biological samples from 15 patients with GBS associated with ZIKV and 17 with ZIKV infection without neurological complications. ZIKV genotypes in Colombia exhibited distribution across three clades (average bootstrap of 90.9±14.9%), with two clades dominating the landscape. A comparative analysis of ZIKV genomes from GBS and non-neurological complications, alongside 1368 previously reported genomes, revealed no significant distinctions between the two groups. Both genotypes were similarly distributed among observed clades in Colombia. Furthermore, no variations were identified in the amino acid composition of the viral genome between the two groups. Our findings suggest that GBS in ZIKV infection is perhaps associated with patient susceptibility and/or other para- or post-infectious immune-mediated mechanisms rather than with specific ZIKV genome variations.